DEWAN ENERGI MAHASISWA: ORGANISASI PEMUDA MASA DEPAN INDONESIA: REFLEKSI 76 TAHUN MENUJU INDONESIA EMAS 2045 - Al Hakim, Rosyid; Juandry, Robi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Student organizations (ormawa, in Indonesian) exist today. Besides improving soft skills competence outside the campus environment, ormawa can be a place to enhance character education. One of the external campus organizations among students to fight for energy in Indonesia is the Student Energy Council (DEM). DEM comes with the educational background of its multidisciplinary and multicultural members to fight for the noble values of the nation. DEM can be a forum for students to contribute to “Indonesia Golden 2045”.